FORMULASI GEL EKSTRAK ETANOL BUAH MAHKOTA DEWA (Phaleria macrocarpa (Scheff.) Boerl) DENGAN VARIASI KONSENTRASI CARBOPOL DAN PROPILENGLIKOL - Nurhaini , Rahmi; Hidayati , Nurul; Hapsari, Lisa Fidy Hapsari (CERATA Jurnal Ilmu Farmasi, 2018)
Mahkota Dewa (Phaleria macrocarpa (Scheff.) Boerl) was a plant that contains many chemical compounds one of which flavonoids. Flavonoids act as an antibacterial acne-causing Staphylococcus epidermidis. Acne can be overcome by using stocks that have good penetration one of which is a gel formulation. The purpose of experiment was to determine the effect of variations in the concentration of carbopol as a gelling agent and propylene glycol as a humectant to the physical properties of the gel and to know gel that produces the most excellent physical properties. This experiment uses ethanol extract of Mahkota dewa (Phaleria macrocarpa (Scheff.) Boerl) as the active ingredient and made five formulas with various concentration Carbopol: propylene glycol is formula I (0.5%: 15%), formula II (0.875%: 13.75%), the formula III (1.25 %: 12.5%), the formula IV (1.625%: 11.25%) and formula V (2%: 10%). Fifth tested formula physical properties and analyzed by ANOVA with confidence level of 95%. The results showed carbopol increase the viscosity and adhesion while propylene glycol improve dispersive power. Formula II and III produces the most excellent physical properties, with a pH test between 4.5 to 6.5, viscosity test 150-200 dPas, 5-7 cm dispersive power test, adhesion > 1 sec and power tests there are no red stain protection. Statistical analysis LSD formula II and III showed no significant differences. Viscosity test and dispersive power indicates with p value of 0.000 (<0.005) and adhesion with p value of 0.007 (<0.05).